2018
DOI: 10.18203/2349-3291.ijcp20182582
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of probiotics in acute diarrhoea in children

Abstract: Background: Gastroenteritis is a major public health problem worldwide and remains the second leading cause of death among children under five globally. Objective of this study was to investigate and compare the efficacy of commonly available probiotics in the treatment of acute watery diarrhoea (AWD) in children.Methods: This was an open label randomised controlled trial conducted in a tertiary care hospital in Bangalore for 2 years. 120 children aged 6 months to 5 years admitted with AWD of less than or equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…This study also showed that both groups reduced the frequency of diarrhoea on Day 4 of treatment and statistically insignificant (p value=0.506). This result was consistent with the study conducted by Sinchana Bhat et al which showed that Bacillus Clausii did not significantly affect duration and frequency of diarrhoea in comparison to control and Saccharomyces Boulardii group 6 . This was supported by Canani RB et al evaluating five probiotic preparations in children with acute diarrhoea proved that only two preperations : L. rhamnosus (LGG) and the mix of (L bulgaricus, L acidophilus, S thermophilus and B bifidum) had a significant effect on reducing the severity and duration of diarrhoea after the first day of administration.…”
Section: Resultssupporting
confidence: 93%
“…This study also showed that both groups reduced the frequency of diarrhoea on Day 4 of treatment and statistically insignificant (p value=0.506). This result was consistent with the study conducted by Sinchana Bhat et al which showed that Bacillus Clausii did not significantly affect duration and frequency of diarrhoea in comparison to control and Saccharomyces Boulardii group 6 . This was supported by Canani RB et al evaluating five probiotic preparations in children with acute diarrhoea proved that only two preperations : L. rhamnosus (LGG) and the mix of (L bulgaricus, L acidophilus, S thermophilus and B bifidum) had a significant effect on reducing the severity and duration of diarrhoea after the first day of administration.…”
Section: Resultssupporting
confidence: 93%
“…12 Another recent study conducted by Bhat S et al, which showed that Bacillus clausii did not significantly affect duration and frequency of diarrhoea in comparison to control and Saccharomyces boulardii group. 13 In this study, Bacillus clausii did not show any significant improvement in term of duration, frequency of diarrhoea and duration of hospital stay, but improved stool consistency one day later than that of multistrains group. Maugo BM conducting a study in under 5 children in Kenya concluded that there was a significant decrease in the frequency of stool on Day 3 and 4 of treatment but no significant difference in reduction of duration of diarrhoea and duration of hospital stay with Bacillus clausii.…”
Section: Discussioncontrasting
confidence: 51%
“…Ultimately, 29 RCTs that randomised 4217 participants (2152 in the experimental group and 2065 in the control group) were included . .…”
Section: Resultsmentioning
confidence: 99%